Jewish reactions to the destruction of Jerusalem in A.D. 70 : apocalypses and related pseudepigrapha - Jones, Kenneth R., Ph. D. (Supplements to the Journal for the Study of Judaism, 2011)
The Roman destruction of Jerusalem in A.D. 70 was a watershed event in the religious, political, and social life of first-century Jews. This book explores the reaction to this event found in Jewish apocalypses and related literature preserved among the Pseudepigrapha (4 Ezra, 2 Baruch, 3 Baruch, 4 Baruch, Sibylline Oracles 4 and 5, and the Apocalypse of Abraham). While keeping the historical context of their composition in mind, the author analyzes the texts with a view to answering the following questions: What do these texts tell us about Jewish attitudes toward the Roman Empire? How did Jews understand the situation in post-70 Judea through the lens of Israel's past, especially the Babylonian sack of Jerusalem in 587 B.C.?